A Spherically Symmetric Solution of \(R+λ R^2\) Gravity - Thang, Bui Quyet; Huong, Do Thi (Communications in Physics, 2014)
We shortly review the metric formalism for the \(f(R)\) gravity. Based on the metric formalism, westudy the spherically symmetric static empty space solutions with the gravity Lagrangian\(L=R+λ R^2\). We found the general metric that described the static empty space with thespherically symmetry. Our result is more general than Schwarzschild solution, specially thepredicted metric is perturbed Schwarzschild metric of the Einstein theory.